Assessment of Atmospheric Metal Pollution Biomonitoring Potential by Neem Tree (Azadirachta indica) Leaves in Katsina Metropolitan Area of Katsina State, Nigeria - A. Fowotade Sulayman; Hamisu Abdu; A. Abdullah Saidu; Fadhila Ahmad; J. Zainab Suleiman; Saleh, Isyaku (Current Approaches in Science and Technology Research Vol. 3, 2021)
The determination of trace metal concentrations in plants and animals has been used as indicator of environmental monitoring. Heavy metals from soil enter plants primarily through the roots system. In general plant roots are the most important site for uptake of chemicals from soil. In this study, the leaves of the neem tree (Azadirachta indica) were used as a bio-indicator to track trace metal levels in the Katsina metropolis. Leaves were sampled from four sites in Katsina metropolis, which include; Site A (Katsina Steel Rolling Company Round-about), Site B (Kofar Kwaya Round-about), Site C (Kofar Yandaka Roundabout) and Site D (Army Barrack, Natsinta). The samples were analyzed for iron, manganese, copper, lead, cobalt, chromium, nickel and zinc using atomic absorption spectrophotometer (AAS). The results obtained across the four sites on the average showed relatively show high levels of iron [93.44 µgg–1], manganese [28.97 µgg–1] and zinc [13.28 µgg–1] over chromium [8.07 µgg–1], cobalt [5.79 µgg–1], lead [2.50 µgg–1], nickel [2.13 µgg–1] and copper [1.70 µgg–1]. The concentrations of iron were also shown to correlate significantly with distance from the Steel Rolling Company. The highest metal loading came from site A, while the lowest came from site D. The results also indicated a somewhat correlation between the metal concentration and distance of each site from the source of contamination (Steel Rolling Company)- Among the trace metal analyzed iron has the highest level while copper has the least. According to the findings, the trace metal burden in Katsina metropolis and its environs poses no imminent hazard to residents or other lives.